Encountering Berlant part two: Cruel and other optimisms. Issue 1 (25th December 2022) - Anderson, Ben; Awal, Akanksha; Cockayne, Daniel; Greenhough, Beth; Linz, Jess; Mazumdar, Anurag; Nassar, Aya; Pettit, Harry; Roe, Emma J.; Ruez, Derek; Salas Landa, Mónica; Secor, Anna; et al.
Abstract: Part 2 of Encountering Berlant amplifies the promise of Lauren Berlant's influential concept of 'cruel optimism'. Cruel optimism names a double‐bind in which attachment to an 'object' holds out the promise of sustaining/flourishing, whilst simultaneously harming. The lines between harming, sustaining, damaging and flourishing blur, sometimes collapsing entirely. By holding together opposites the concept exemplifies and performs the centrality of ambivalence to Berlant's thought, as well as their orientation to overdetermination and incoherence. Geographers and others have found in the concept a way of understanding the intersection between affective and political economies in the crisis‐present following the 2008 financial crisis. Together with Berlant's linked concepts such as 'crisis ordinariness' and 'impasse', cruel optimism has offered a way of understanding why detachment can be so difficult and how damaging conditions endure. Contributors begin from these starting points, amplifying the concept's promise: a new way of researching and writing about the reproduction of ordinary damage and harm. By writing from diverse encounters with Berlant's work, they move the concept in multiple directions, juxtaposing it with other optimisms across a variety of empirical scenes and locations. The result is a repository of what cruel optimism, and Berlant's mode of thinking‐feeling more broadly, offer geographers and others. Short Abstract: In Part Two of Encountering Berlant, contributors engage with the promise of Lauren Berlant's most influential concept – 'cruel optimism'. By writing from multiple locations and empirical scenes, they find in the concept a new way of understanding the reproduction of everyday harms and damages.